2009
DOI: 10.1111/j.1439-0531.2007.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Content of Non‐cultured and Cultured Pig Embryo

Abstract: The objectives of the study were: (i) to work out a precise and efficient method for quantitative analysis of lipid content and (ii) to quantitatively determine the lipid content in non-cultured and cultured pig embryos. The experiment was carried out on pig embryos from zygote to late blastocyst stages produced in vivo and embryos collected at the zygote stage and then cultured in vitro up to blastocyst stage. Embryos were fixed, dehydrated, embedded in epoxy resin and cut into semi-thin sections to analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Elevated LD content has been associated with suboptimal embryo health and increased cryo-sensitivity in bovine embryos [38]. In porcine embryos, in vitro cultured embryos had more LD than non-cultured (presumably healthier) embryos [39]. THG can be used to quantify LD volume and number in live embryos without staining, providing objective criteria for assessing embryo quality.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated LD content has been associated with suboptimal embryo health and increased cryo-sensitivity in bovine embryos [38]. In porcine embryos, in vitro cultured embryos had more LD than non-cultured (presumably healthier) embryos [39]. THG can be used to quantify LD volume and number in live embryos without staining, providing objective criteria for assessing embryo quality.…”
Section: Discussionmentioning
confidence: 99%
“…Others suggest that they are needed as a lipid source for cell division (Yoneda et al 2004). Lipid content depends on the stage of embryo development, significantly decreasing after the morula stage (Romek et al 2009), thus making early stages more susceptible to low temperatures. Following the observation that embryos with high intracellular lipid content are more prone to cryoinjury, at least three methods to manipulate these lipid droplets have been attempted.…”
Section: Intracellular Lipidsmentioning
confidence: 99%
“…The low cryotolerance (Sudano et al 2014) and cell degeneration (Huang et al 2010) observed in these embryos correlate with differential expression of genes involved in lipid biosynthesis and cholesterol metabolism (Van Hoeck et al 2015). Such effect could be due to any of the various factors present in serum (glucose, lipids, growth factors) (Leroy et al 2010), and some studies have shown that the lipid fraction of serum increases the triglyceride and cholesterol contents of IVC embryos (Abe et al 2002, Romek et al 2009.…”
Section: Response To Energetic Stressmentioning
confidence: 99%
“…Accumulating of evidence shows that IVC embryos bear the hallmarks of energetic stress in terms of nutrient utilisation (increased conversion of glucose to lactate), nutrient storage (lipid accumulation) and ATP synthesis (Spielmann et al 1984, Thompson et al 1991, Van Blerkom et al 1995, Khurana & Niemann 2000, Swain et al 2002, Romek et al 2009). This metabolic state occurs because of inadequate support in the in vitro environment.…”
Section: Response To Energetic Stressmentioning
confidence: 99%
See 1 more Smart Citation